2017
DOI: 10.3389/fbuil.2017.00033
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties of Treated Natural Hemp Fiber-Reinforced Concrete

Abstract: In recent years, the construction industry has seen a significant rise in the use of natural fibers, for producing building materials. Research has shown that treated hemp fiberreinforced concrete (THFRC) can provide a low-cost building material for residential and low-rise buildings, while achieving sustainable construction and meeting future environmental targets. This study involved enhancing the mechanical properties of hemp fiber-reinforced concrete through the Ca(OH) 2 solution pretreatment of fibers. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The authors reported that the flexural strength in both alkaline- and water treated fiber composites achieved similar values (around 8 MPa). On the other hand, Zhou et al [ 136 ] evaluated the behavior of cement composites reinforced with hemp fiber. The hemp fibers were treated with a 2 wt.% Ca(OH) 2 alkaline solution for 14 h. The authors reported that treated hemp fiber-reinforced composites showed higher compressive strength, tensile strength and fracture toughness by 10%, 17%, and 7–13%, respectively, in contrast to unmodified fiber composite.…”
Section: Pre-treatments Of Natural Fibers Used As Reinforcement Inmentioning
confidence: 99%
“…The authors reported that the flexural strength in both alkaline- and water treated fiber composites achieved similar values (around 8 MPa). On the other hand, Zhou et al [ 136 ] evaluated the behavior of cement composites reinforced with hemp fiber. The hemp fibers were treated with a 2 wt.% Ca(OH) 2 alkaline solution for 14 h. The authors reported that treated hemp fiber-reinforced composites showed higher compressive strength, tensile strength and fracture toughness by 10%, 17%, and 7–13%, respectively, in contrast to unmodified fiber composite.…”
Section: Pre-treatments Of Natural Fibers Used As Reinforcement Inmentioning
confidence: 99%
“…Several studies demonstrate the use of chemical surface treatments on cellulosic fibers to reduce their hydrophilic character and improve their adhesion properties with the matrix [ 104 , 105 , 106 ]. Most works with lignocellulosic fibers in cementitious matrices are based on treatments with alkaline solutions: Ca (OH) 2 , NaOH, KOH, LiOH, Na 2 CO 3 [ 14 , 53 , 97 , 106 , 107 , 108 , 109 ]. The chemical treatment involves modifying the fiber’s hydroxyl groups and introducing other interacting groups that effectively interconnect with the matrix at the interface.…”
Section: Why Are Natural Fibers Treated For Application In Cementitio...mentioning
confidence: 99%
“…In biomedical applications, natural fibers are in fiber-reinforced composites (FRC), such as various clinical fields [172] as described in Table 2. Hemp and sisal have been reported for utilization as cementitious construction and fancy materials in the construction field [173,174]. In the biomedical field, the most promising natural fiber candidate is undoubtedly cellulose, in the form of nanofibers.…”
Section: Social and Economic Aspects On Utilization Of Natural Fibersmentioning
confidence: 99%